Ruang Terbuka Hijau Layak Anak - La Ode Anhusadar (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This study aims to determine the condition of open green space in Kendari city, the use of green open space in Kendari city and the role of green space towards the growth of children to support and realize Kendari City as a child-friendly city. This study uses qualitative research. parents want every facility in the park to be good and decent, the game in the city park is quite a lot, but most of the game is damaged and not suitable for use.